UPAYA FORUM KOMUNIKASI MASYARAKAT PEDULI LINGKUNGAN DALAM MEMPERJUANGKAN PEMENUHAN HAK ATAS PEKERJAAN - Nurmasari, Ervina Desy; Setyowati, Rr Nanik (Kajian Moral dan Kewarganegaraan, 2023)
This research analyzes the efforts of the Selok Awar-awar Village Environmental Care Community Communication Forum in obtaining the Right to Work after the illegal iron mine caused severe environmental damage. The research location is Selok Awar-awar Village, Pasirian District, Lumajang Regency. Using a research method with a qualitative approach and case study research design. This research focuses on the efforts made by the forum to regain their jobs after the illegal iron sand mine in the village and the obstacles experienced by the forum when seeking this. Data collection techniques include observation, interviews and documentation. The theory used is Biddle and Thomas' theory, which is about the role of a person, group of people, or organization in influencing other groups to follow the norms that apply in society. The results of this study show that the Selok Awar-awar Village Environmental Care Community Communication Forum has attempted to fight for the Right to Work by restoring the function of rice fields and improving the Watu Pecak Beach tourism area. The obstacles experienced by the forum are security and capital to start a new business. Keywords: Forum Efforts, Employment, Environmental Care